Students' Perceptions of Kahoot as an Online Quiz Tool in Intensive English Class - Elsa Rosalina; Nasrullah Nasrullah; Rahma Pitria Ningsih (Universitas Tidar, 2023)
Online learning media is one of the tools which can support the teaching and learning process. Kahoot, Quizizz, Padlet, and learning Apps are examples of online learning media. Hence in this study, the researchers wanted to find out about the students' perceptions of online quiz applications or better known as Kahoot. This study employed a descriptive quantitative approach because the researchers described students' perceptions of Kahoot as an online quiz for teaching and learning English in class. Thirty-nine English Department, Lambung Mangkurat University students were selected as the samples in this study from the 2019 Intensive English Class. The instruments used in this study consisted of questionnaires with five answers: strongly agree, agree, neutral, disagree, and strongly disagree. The questionnaire was made and spread online by using Google Forms. The data was analyzed quantitatively using the implementation of a Likert scale. The findings show that the students' perceptions of Kahoot as an online quiz tool are positive. It can be seen from the score of instruments distributed by the researchers. The score gets 2.192 from 2.730 as the maximum score. The maximum score was gotten from (Q1: number of students, K: maximum score for each question and Q: number of questions) = 39 x 5 = 195 x 14 = 2.730, which means that Kahoot is a good online quiz application for teaching English in Intensive English Class based on students' perceptions. Most of the students agree that the process of teaching and learning via Kahoot as an online quiz tool is interesting, motivating, and fun. They also agree that they feel a positive effect on using its application and try to repeat to play Kahoot.